Estado de la Colección de Palmas (Arecaceae) del Herbario Cyril Hardy Nelson Sutherland (TEFH), Honduras - Rodriguez, Maynor J. (2025)
The "Cyril Hardy Nelson Sutherland" Herbarium (TEFH) holds a remarkable collection of 317 palm specimens up to March 2024, comprising a total of 73 species, including 14 non-native species to Honduras. Notable specimens include Chamaedorea moliniana and Cryosophila williamsii, two of the three endemic palm species recorded in Honduras. The most represented species are Chamaedorea costaricana, Chamaedorea neurochlamys, and Chamaedorea pinnatifrons. Dr. Cyril H. Nelson Sutherland is the primary contributor with 123 samples, equivalent to 38.8 % of the total. Samples collected by Dr. Fred A. Barkley in 1970 are the oldest of Honduran palms in this herbarium. The collection comprises 2 subfamilies, 30 genera, and 73 species, distributed in 16 of the 18 departments of the country. The main departments of Honduras where palms have been collected are Atlántida, Gracias a Dios, Olancho, and Cortés. The main purpose of this study is to disseminate the findings derived from the evaluation conducted on the palm collection (Arecaceae) at the TEFH herbarium, this marking the beginning of the exploration of the current state of this family in Honduras.